Rights of fetus in Muslim jurisprudence - Shuriye, Abdi Omar (2007)
Fetus is the later phases of the unborn offspring. It is a scientific term coined to describe the period of the unborn after the embryonic stage. From conception to the eighth week the development of the offspring is known an embryo. Muslim Jurisprudence regards the Janin (fetus) as the first unit of human being; as such, it grants protection and reverence, it also confers a wide range of rights in order to safeguard the development, welfare and the security of the fetus. This paper aims to explore the rights bestowed on the fetus by Muslim jurisprudential previsions. Muslim jurisprudence makes a binding duty on the father to provide for his divorced pregnant wife; also the pregnant mother is exempted from the daily and monthly obligatory religious rituals. Severe punishments should not be carried out during pregnancy, in fact, if a pregnant mother is condemned to death by a court of law, execution is deferred until delivery and breast-feeding fulfilled. In the opinion of the mainstream Muslim jurists marriage is not permitted for a pregnant mother, this is to further protect the identity of the fetus.